2022
DOI: 10.23917/jep.v23i1.17673
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Macroeconomic Indicators on Indonesia’s Foreign Exchange Reserve Position

Abstract: A country’s foreign exchange reserves are its foreign currency savings that can be utilized to finance international transactions. The purpose of this study is to determine how macroeconomic indicators (exports, imports, exchange rates, inflation rates, and foreign debt) influence Indonesia’s foreign currency reserves. The researchers used secondary data in the form of monthly time series, as well as quantitative analysis using multiple linear regression. The model that was used was the Vector Error Correction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
1
0
1
Order By: Relevance
“…The results of this study are in line with research conducted by Anwar et al, (2019) which showed that exports had a positive and negative effect on exports. The results of this study are supported by research conducted by (Rahmawati & Suriani, 2022).…”
Section: Effect Of Exports On Foreign Exchange Reservessupporting
confidence: 84%
See 1 more Smart Citation
“…The results of this study are in line with research conducted by Anwar et al, (2019) which showed that exports had a positive and negative effect on exports. The results of this study are supported by research conducted by (Rahmawati & Suriani, 2022).…”
Section: Effect Of Exports On Foreign Exchange Reservessupporting
confidence: 84%
“…While research from Juliansyah, Moulida, and Apridar (2020) found that exports had a negative effect on foreign exchange reserves. Based on research conducted by Anwar et al(2019) and Rahmawati & Suriani(2022)found that exports have a positive effect on foreign exchange reserves.Export activities are in contrast to import activities. The MABP theory reveals that when there is an increase in imports, the stock of nominal domestic money will decrease (Masdjojo, 2010).…”
Section: Empirical Studymentioning
confidence: 99%
“…Ekspor merupakan sebuah motor penggerak perekonomian nasional yang menjadi salah satu komponen dalam menyumbang pendapatan nasional. Ekspor dapat menstimulasi pertumbuhan ekonomi melalui peningkatan Produk Domestik Bruto (PDB) (Rahmawati dan Suriani, 2022). Selain itu, naiknya aktivitas ekspor juga mampu menurunkan jumlah kemiskinan karena dapat menggerakan roda perekonomian dalam berbagai ruang lingkup ekonomi (Waheed, 2017).…”
Section: Pendahuluanunclassified